Penetapan Kadar Protein Dalam Telur Unggas Melalui Analisis Nitrogen Menggunakan Metode Kjeldahl - Dwi Dinni Aulia Bakhtra; Rusdi Rusdi; Aisyah Mardiah (Jurnal Farmasi Higea, 2016)
Eggs consumed by many people because it’s easily to processed, low cost, and have perfect substances, especially proteins. The purpose of this research were to determine levels of the protein in the fowl’s eggs. The sample used in this research are rooster chicken egg, ayam kampung egg, duck egg, and quail egg. The protein content in fowl’s eggs were evaluated using Kjeldahl method by calculating the total nitrogen content and converted (conversion factor is 6.25). Result of the research protein content contained in rooster chicken egg 6.4506 % ± 0.1418, ayam kampung egg 6.9102 % ± 0.0475, duck egg 6.5996 % ± 0.0497, and quail egg 6.5532 % ± 0.0110. The result of the test statistics clarify that the sample eggs are examined to contain the protein with the levels of different significantly (F = 94.461 and sig. 0.000 (<0.05)). Where ayam kampung egg have protein content higher than another eggs sample and the lowest protein content contained in rooster chicken egg.